Aplikasi Penentuan Harga Perkiraan Sendiri Proyek Pengembangan Perangkat Lunak Kepemerintahan Berbasis Web - Dony Purwanto; Arifin Puji Widodo; Teguh Sutanto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Owner Estimate (OE) is the price of goods or services what is calculated based on the expertise and data that can be accounted for. Determination of OE for software projects until now is guided by the Indonesia Presidential Decree No. 70 of 2012, which only describes OE for the procurement of goods, construction projects, consulting services, and procurement of other services. In that regulation does not specifically explained the determination of OE for the software project. So in this case Committing Officer (CO) as a constituent of OE have adversity to determining OE for software development projects. Based on these problems then built the application of determining owner estimates (OE) price for the web-based software development projects, which the method calculation used for effort estimation is Use Case Points (UCP). Built application will be able to perform the calculation of Unadjusted Actor Weight (UAW), unadjusted Use Case Weight (UUCW), Technical Complexity Factor (TCF), and the Environmental Complexity Factor (ECF). Then from these values, the application will calculate the effort estimation that continued with the process of calculating the direct costs of personnel. Further, the application can also calculate the direct non-personnel costs, profits, taxes, up to the cost estimation. From the testing and evaluation conducted, the application can generate value Unadjusted Actor Weight (UAW), Unadjusted Use Case Weight (UUCW), Technical Complexity Factor (TCF), Environmental Complexity Factor (ECF), effort estimation, direct cost of personnel, direct cost non-personnel, profits, taxes, and cost estimation. So that can be concluded that application can be used to calculate the price of Owner Estimate (OE) for software development projects of small and medium-scale governance.